Bullying of postgraduate medical trainees in tertiary care hospitals - Hussain, Shahzadi Saima; Rahim, Rehana (Journal of Postgraduate Medical Institute, 2014)
Objective: To determine prevalence of bullying among postgraduate medical trainees in tertiary care hospitals in Peshawar. Methodology: This cross-sectional study of postgraduate medical trainees from different specialties was conducted in three tertiary care hospitals of Peshawar using convenience sampling. A semi structured questionnaire containing questions regarding type of bullying, who perpetuates bullying and effect of bullying was filled by the participants. The results are expressed in the form of frequency and percentages. Results: Out of 246 Postgraduate medical trainees who responded to semi structured questionnaire, 89% (n=219) reported being bullied in one or more forms, Overload with work was reported by 83% (n=203) as most common type of bulling. The common perpetrator of bullying were registrars, senior registrars were mentioned by 20% (n=49), while 18% (n=44) thought junior registrars are bullying them. The effect of bullying was that 31% (n=71) were depressed because of bullying. Conclusion: Bullying of Postgraduate medical trainees is fairly common in hospitals and registrars are most commonly involved as perpetrators. More awareness should be created about bullying and feedback about working environment should be regularly obtained from postgraduate medical trainees.